Characterization of the long-term toxic response of proximal tubule epithelial cells in a microphysiological system - Abuhamad, Yousif (My University, 2024)
Kidney diseases impact 850 million people globally, with 1 in 7 US adults affected, making it the 9th leading cause of death. Factors such as genetic variability, co-occurring health conditions, and exposure to drugs and environmental chemicals contribute to kidney diseases, which may take months or years to manifest clinically. Existing research lacks effective strategies, assays, and models for assessing human acute and chronic in vitro kidney toxicity, leading to research gaps in the nephrotoxicity of xenobiotics. Identification of potential kidney toxicants can help reduce the incidence of kidney disease. Organs-on-chips or microphysiological systems (MPS) are innovative microfluidic models to enhance our understanding of xenobiotic effects on kidney function. Previous studies from our group replicated toxic responses in kidney proximal tubule epithelial cells (PTECs); however, this was limited to acute exposures (2-10 days). To assess the applicability of our PTEC MPS in chronic toxicity testing, we conducted temporal studies using 50 μM polymyxin B (PMB), a known kidney toxicant, at baseline and 2.5, 5, and 6 months after cell seeding. Toxic response was measured through kidney injury molecule-1 (KIM-1) and interleukin-6 (IL-6) concentrations in effluent, coupled with global transcriptome profiles. We observed a decrease over time in the magnitude of injury markers and genes of toxic exposure in response to acute PMB exposure. This suggests that response to toxicity decreases in older PTEC MPS devices; however, a toxic response was still detected. Furthermore, we cultured PTEC MPS devices beyond 6 months to determine the limits of PTEC MPS viability. The PTEC MPS have remained structurally stable for over 13 months as evaluated by brightfield microscopy. Our results suggest that PTEC MPS can potentially be used to evaluate chronic exposures for up to a year, given that a decrease in toxic response over time is considered. PTEC MPS can potentially be used for the prediction of nephrotoxicity by chronic exposure to low concentrations of xenobiotics.
Thesis (Master's)--University of Washington, 2024
Keywords: Toxicology; Environmental health; Environmental health